PENGARUH PENGGUNAAN TIPE ELEKTROLISER DAN JENIS LARUTAN PADA HYDROGEN ECO BOOSTER TERHADAP EMISI GAS BUANG SEPEDA MOTOR 4 TAK - Abdul ‘Aziz Manggala Saputra; Ranto Ranto; Basori Basori (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2019)
The purpose of this research are: (1) Investigate the influence of the type of electrolyzer on Hydrogen Eco Booster towards the level of exhaust emissions (CO and HC) 4 stroke motorcycle. (2) Investigate the influence of the kind of solvent on Hydrogen Eco Booster towards the level of exhaust emissions (CO and HC) 4 stroke motorcycle. (3) Investigate the influence of the type of electrolyzer and the kind of solvent on Hydrogen Eco Booster towards the level of exhaust emissions (CO and HC) 4 stroke motorcycle. This research was conducted at the Automotive Laboratory of Mechanical Engineering Education, Teacher Training and Education Faculty Sebelas Maret University of Surakarta used a Honda Supra X 125 motorcycle, year of manufacture 2013. This study is an experimental research. The method of collecting data used in the research is measurement method. The data obtained from the test results were analyzed using Two-Way Anova Test and followed by One-Sample T Test and Scheffe Test. The results of this research are: (1) There is a significance effect on the type of electrolyzer on Hydrogen Eco Booster towards to decrease the level of exhaust emissions (CO and HC) 4 stroke motorcycle, (Sig-value of CO gas=0.001 < α=0.05) and (Sig-value of HC gas=0.000 < α=0.05). (2) There is a significance effect on the kind of solvent on the Hydrogen Eco Booster towards to decrease the level of exhaust emissions (CO and HC) 4 stroke motorcycle, (Sig-value of CO gas=0.000 < α=0.05) and (Sig-value of HC gas=0.000 < α=0.05). (3) There is a significance effect interaction between the type of electrolyzer and the kind of solvent on the Hydrogen Eco Booster towards to decrease the level of exhaust emissions (CO and HC) 4 stroke motorcycle, (Sig-value of CO gas=0.000 < α=0.05) and (Sig-value of HC gas=0.000 < α=0.05). The lowest CO gas obtained on the Wet Cell type using the kind of solvent KOH with a decrease of 84.41%. The lowest HC gas obtained on the Dry Cell type using the kind of solvent NaOH with a decrease of 69.62%.